Comic Life and Cartoon Story Maker in Creating Short Story for Young Learners - Lystiana Nurhayat Hakim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The aims of this study is to find out TEYL students’ perception and experience in using Cartoon Story Maker and Comic Life in creating short story for young learners and to identify their obstacles and problems in using those applications. This qualitative study has been conducted in a TEYL class in one English Department in West Java. The sample of the study consisted of thirty students. Questionnaires and interviews were used as data collection techniques in this study. The questionnaires were used to collect evidence from students about their experience and perception towards the use of CSM and Comic Life in creating short story for young learners. The questionnaires used in this study focus on exploring students’ experience and perception toward the use CSM and Comic Life in creating short story for young learners, whereas  interview was used to explored more the data about obstacles faced by the students in using CSM and Comic Life. The data collected from the respondents were gathered together to be analyzed using qualitative analysis of interactive models. The results of this study are TEYL students have positive perception toward the use of CSM and Comic Life in creating short story for young learners, CSM is easier and more suitable to use than Comic Life in creating story for young learners, and the obstacles faced by students are choosing appropriate template for young learners, writing text in text tool or bubble, and record the voice in audio bubble.